Seroprevalaııce of brucella ovis infection in rams from some flocks in the provinces konya and sivas - Uçkun Sait UÇAN; Zeki ARAŞ (Eurasian Journal of Veterinary Sciences)
Brucella ovis causes epididymitis in rams, abortions in ewes and an increased neonatal mortality in lamb. Because of atypical clinical findings of B. ovis infections in rams that can be shared with some other genital infections, difficulties with isolation and identification of the causative and its time-consuming pocedure, serology is widely used to diagnose the disease in the field A number of 264 blood serum samples collected from 35 flocks were examined by Modified Micro Plate Agglutination Technique (MPAT) in which an antigen prepared from B. can is NCTC 10854 in order to determine the frequency of the disease in the flocks from provinces Konya and Sivas. Of the sera, 149 (56,4%) were positive and 115 (43,6%) negative. Seropositives for the flocks from Konya and Slvas were 35,5% and 46,6%, respectively. We believe that the higher infection rate in the flocks needs to be further evaluated with taking a criteria to account that it might be endemic if so which could only be determined by annual examinations of the flocks from now on.